Delving into the green growth dilemma and ESG investing in Southeast Asia - Ting Dai (Humanities & Social Sciences Communications)
Abstract This academic study examines the connection between ESG (Environmental, Social, and Governance) investing and green growth advancement in Southeast Asia, highlighting the region’s susceptibility to environmental pollution. ESG investing proves to be an effective policy tool for sustainability, with a 1% increase in environmental investment linked to a 0.56% rise in the Green Growth Index. However, GDP growth negatively affects the index, indicating a need to harmonize economic and sustainable development goals. Additionally, larger populations and more registered vehicles hinder green growth, requiring detailed policy measures. Internet connection speed has minimal impact. To promote green growth, Southeast Asian nations should prioritize ESG investing, create transparent policies, offer tax incentives, and partner with financial institutions. Policies must aim to separate GDP growth from environmental harm, support sustainable development, and address population and vehicle-related issues through strategic urban planning. While internet speed’s effect is negligible, advancing digitalization is crucial for sustainability via improved technology infrastructure and digital literacy programs.